CRITICAL NURSES’ EXPERIENCE WHILE PERFORMING CPR AT HOSPITAL X BATAM - Nurhaliza.Z, Septi; Natalia, Siska; Suangga, Fitriany (Universitas Pelita Harapan, 2024)
Cardiac arrest is one of the leading life-threatening emergencies, requiring life-saving procedures commonly known as Cardiopulmonary Resuscitation (CPR). In hospitals, nurses are the first responders to cardiac arrest cases. The success of CPR is greatly influenced by several factors that affect nurses' ability to act in emergency situations. This study aims to explore the in-depth experiences of nurses while performing CPR at X Hospital Batam. The research involved 10 critical care nurses, recruited through snowball sampling, with data saturation being achieved. In-depth semi-structured interviews were conducted, audio-recorded, and transcribed verbatim to collect the data. The data were analyzed using Colaizzi’s method of analysis. The findings of this study identified five key themes: The Important Role of Nurses during CPR, Accuracy in Therapy Administration, Nurses' Experiences of Pleasant and Unpleasant Emotions, Expectations of CPR Success, and Focusing on the Patient during Family Presence in CPR, among others. In conclusion, the study highlights the diversity of feelings, experiences, abilities, and knowledge that critical care nurses encounter while performing CPR at X Hospital Batam.